Making Sense of Disinformation in the Swedish Heterogenous Society: Understandings, Experiences, and Vulnerabilities - Maja Klinga; Minna Lundgren (Journal of International Crisis and Risk Communication Research, 2024)
In this paper, we provide knowledge about how people make sense of disinformation in the Swedish heterogenous society. Departing from a bottom-up perspective, we draw on individual interviews and focus groups to capture the experiences and practices vis-à-vis disinformation. We analyze the results using the theoretical concepts of sensemaking and vulnerability. The results indicate that there are differences in how people make sense of and act in relation to disinformation depending on age, educational background, and previous experiences. Furthermore, the results indicate that crises and uncertain times make people more vulnerable to disinformation. We argue that disinformation can be viewed both as a risk and as a crisis in itself. We conclude that lack of adequate information from trusted sources during crises and disasters makes people more exposed to and more vulnerable to disinformation.